2023
DOI: 10.3390/su15010873
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Potential and Agribusiness Desirability among Youths in South Kivu, Democratic Republic of the Congo

Abstract: In the Democratic Republic of Congo (DRC), entrepreneurship in the agriculture sector remains for youth a key pillar for income creation. However, few are attracted by agribusiness despite stakeholders’ efforts toward engaging youth in agriculture. Therefore, this study examines the relationship between entrepreneurial potential characteristics and youth desirability to start an enterprise in agriculture among 514 young people in Eastern DRC. This study revealed that youth in South Kivu have different entrepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Global Journal of Humanities and Social Sciences eISSN: 2957-3602 pISSN: Page No. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Results of the study revealed significant relationship in the level of entrepreneurial skills and entrepreneurial orientation, this denotes that each unit of improvement in entrepreneurial skills and orientation increases entrepreneurial resilience. However, entrepreneurial orientation could be better determining entrepreneurial resilience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Global Journal of Humanities and Social Sciences eISSN: 2957-3602 pISSN: Page No. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Results of the study revealed significant relationship in the level of entrepreneurial skills and entrepreneurial orientation, this denotes that each unit of improvement in entrepreneurial skills and orientation increases entrepreneurial resilience. However, entrepreneurial orientation could be better determining entrepreneurial resilience.…”
Section: Discussionmentioning
confidence: 99%
“…According to Nawaz, (2023), entrepreneurs Global Journal of Humanities and Social Sciences eISSN: 2957-3602 pISSN: Page No. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] need to be resilient in order to cope and adapt with constantly changing business environment and withstand any disruptions. Entrepreneurial resilience can boost agricultural entrepreneurs' performance and success in a variety of ways.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, this study conforms to the Theory of Reasoned Pursuit of Goals (TRGP) of Ajzen and Guglanski [40] in such a way that it applies Climate Smart Integrated Pest Management (CS-IPM). In addition, the motivation to engage in a certain type of farming activity is largely influenced by the perception of the possibility that using farming expertise would result in success in achieving agri-food development goals [40,41]. Literally, smallholder farmers might be motivated when the choice may have positive social, environmental, and welfare effects to being entities profit maximizing [9,14,19,21].…”
Section: Climate-smart Agriculture Integrated Pest Management (Cs-ipm...mentioning
confidence: 99%